Preliminary Phytochemical Analysis and Invitro Antiplasmodial Activity of Terminalia mantaly Against Plasmodium falciparum - Usman, Bello Muhammad; Attah, Daniel Dan-Inna; Kanya, Danladi Yusuf (Folia Medica Indonesiana, 2022)
Highlights: • Malaria is prevalent in many populations of communities despite preventive measures. • The experimental was screened for bioactive components which could be the reason for the antimalarial effect and the plant shows dose dependent antimalarial activity. Abstract : Malaria has been one of the world's worst killer diseases throughout recorded human history. Despite attempts to eradicate the disease, it remains a global burden. This could be a result of parasite resistance to current therapy. However, this research aimed at evaluating the in vitro antimalarial activity of ethanolic extracts of Terminalia mantaly on Plasmodium falciparum. The plant extracts were prepared by cold maceration in 70% ethanol and air-dried by a rotary evaporator. The phytochemical analysis was carried out using standard procedures outlined in the Analytical methods of the Association of Official Analytical Chemists (AOAC, 1990) which indicates the presence of tannins, alkaloids, saponins, flavonoids, glycosides, phenol, steroids, and balsam. The in vitro antimalarial assay was carried out according to the method described by WHO (2001). All data were represented as Mean ± Standard deviation. Ethanolic extracts of the three parts of the plant were subjected to in vitro antimalarial activity at three concentrations (300 mg, 150 mg, and 75 mg) in four replicates with artemether (standard drug) as a positive control. Stem bark at 300 mg/kg completely cleared the parasites with a 0.00% parasitaemia rate and there was no significant difference when compared with positive control at p<0.005 value of 1.00. This study affirms the use of the plant for the treatment of malaria.